Optimasi Produksi Pada Produk Tahu di CV Maik Meres Dengan Menggunakan Metode Simpleks Linear Programming (International Forum of Researchers and Lecturers, 2023)
Tofu is a food that is in great demand by the people of Indonesia because it tastes good and the price is relatively cheap. One of the businesses that is active and has a sizeable market potential on the island of Sumbawa, NTB is CV Maik Meres which is located in the Brang Biji village, Sumbawa sub-district. CV Maik Meres is an industry engaged in processing soybeans with 37 kg of large white tofu and 33 kg of small white tofu in one production as the main raw material for tofu products. The purpose of this study was to find out the effective optimization of the production process to be carried out by CV maik meres using the simplex linear programming method. Before using the simplex linear programming method, CV Maik Meres produced 20 prints for large white tofu and 10 prints for small white tofu. From the results of research using QM software for Windows V5, it resulted in an optimization of the production process for large tofu as much as 40,74 prints and did not produce small tofu to get a maximum profit of Rp. 361,166,7 in one production. So that the maximum profit of CV Maik Meres in one production is Rp. 188,440,7 and an increase of 19% from factual conditions.